Les paysages épongent : entre écologie et conception, amorcer une recherche transformative sur la Zone Atelier Plaine et Val de Sèvre - Alexis Pernet (Projets de Paysage)
The many protests spurred by the climate crisis and the timid responses of societies so far have brought about changes in research standards and practices. As a response to the calls for the deployment of nature-based solutions, the landscape provides an answer in terms of the scale and scope for action that scientific research can demonstrate provided a long-term approach is made possible by a dedicated experimental infrastructure. Objectives for the transformation of landscapes and ecosystems can therefore be pursued in zones able to demonstrate the interactions between science and society. This article takes as a starting point the conflict over the “megabasins” in the Poitou region and the presence of the long-term research infrastructure of the Zone Atelier Plaine et Val de Sèvre as an example of the emerging trend of “transformative” research. It presents the initial results of “Les paysages épongent” (literally “the spongescapes”) project that establishes links between the tools of landscape architecture and ecology and the slowing down of the water cycle.